Preschool group practices and preschool children's sedentary time: a cross-sectional study in Finland. Issue 12 (17th December 2019) - Määttä, Suvi; Lehto, Reetta; Konttinen, Hanna; Ray, Carola; Sajaniemi, Nina; Erkkola, Maijaliisa; Roos, Eva
Abstract : Objectives: Preschool is an important setting for regulating sedentary time (ST). The preschool day in Finland follows daily structures by having morning and afternoon slots for group-based activities that can encourage children for movement (eg, free play and outdoor time) or be still (eg, teacher-led sessions and sitting-based circles). This study aims to explore if the weekly routines in preschool and if more frequent visits in places encouraging physical activity (PA) are associated with children's ST during preschool hours. Design: Cross-sectional DAGIS (Increased Health and Wellbeing in Preschools) study in the years 2015 and 2016. Setting: In Finland. Participants: 864 children (48% girls, 4.7 years) from 159 preschool groups in 66 preschools Outcome measures: A total of 778 children wore required lengths of time (at least 240 min per preschool day, at least 2 days) the accelerometer during preschool hours. Each preschool group reported their weekly schedule during the week, and one early educator completed a questionnaire covering practices. The following five measures related to weekly structures were formed; times of outdoors (times per day), teacher-led sessions (times per day), free play (low, middle or high), organised PA lessons (no lessons at all/others) and mixed activities (no lessons at all/others), and the following five measures about the frequencies of visits in places encouraging PA; nature trips (times per week), play parks (times per week), neighbourhood sport facilities (no visits at all/others), visits to gym or other indoor facility (no visits at all/others) and field trips to neighbourhoods (times per week). Multilevel linear regression analyses were conducted to measure the associations. Results: Of all the tested associations, only more frequently conducted nature trips were associated with lower children's ST during preschool hours (β=−1.026; 95% CI −1.804 to −0.248). Conclusion: Frequent nature trips in preschools may be important due to its association with lower preschool children's ST.